Nazhir Image and Wakif Trust, Which Influences the Wakif’s Intention to Give Waqf? - Shinta Lintang Nurillah; Yan Putra Timur; Achmad Yasin (Asosiasi Fakultas Ekonomi dan Bisnis Indonesia, 2022)
This study aims to analyses the influence of nazhir image and wakif trust on waqf intentions and decisions. This study uses a quantitative method using the PLS-SEM approach. The primary data is obtained through a questionnaire given to respondents online. The number of sample data used is 100 people. Indicator measurement for each variable uses 5 Likert scales. The study results show that nazhir image and wakif trust have a positive and significant effect on waqf intention. Likewise, with nazhir image also has a positive and considerable influence on waqf decisions. The results of this study provide practical implications, especially for nazhirs to always be able to maintain their trust and image through transparency in the management of waqf funds and the implementation of innovations in the direction of waqf funds so that wakifs can endow waqf through nazhir in the long term.